2020
DOI: 10.1097/cad.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of cetuximab-containing chemotherapy after immune checkpoint inhibitors for patients with squamous cell carcinoma of the head and neck: a single-center retrospective study

Abstract: Immunotherapy has been shown to prolong survival in recurrent or metastatic squamous cell carcinoma of the head and neck (SCCHN) in front-line use; however, subsequent systemic therapy has not been optimized. This study aimed to evaluate the safety and efficacy of cetuximab-containing chemotherapy after immunotherapy. We retrospectively analyzed patients with recurrent or metastatic SCCHN who underwent cetuximab-containing regimens after progression on immunotherapy. Of the 22 patients who met the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In the present study, despite 72.7% of patients receiving nivolumab as second-or later-line treatment [5], paclitaxel ± cetuximab as subsequent chemotherapy demonstrated favorable effectiveness, which was consistent with the findings of a previous study that investigated a combination of paclitaxel and cetuximab as first-line treatment [19]. Several small retrospective studies in Japanese patients with R/M SCCHN have also reported the effectiveness of chemotherapy following treatment with immune checkpoint inhibitors [7][8][9].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, despite 72.7% of patients receiving nivolumab as second-or later-line treatment [5], paclitaxel ± cetuximab as subsequent chemotherapy demonstrated favorable effectiveness, which was consistent with the findings of a previous study that investigated a combination of paclitaxel and cetuximab as first-line treatment [19]. Several small retrospective studies in Japanese patients with R/M SCCHN have also reported the effectiveness of chemotherapy following treatment with immune checkpoint inhibitors [7][8][9].…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies have demonstrated the efficacy of subsequent chemotherapy following immunotherapy in patients with HNC [6][7][8][9]. A previous study reported a significantly longer OS (7.8 months, P = 0.0028, n = 25) in Japanese R/M SCCHN patients who received salvage chemotherapy following nivolumab treatment than that in patients who received best supportive care (3.5 months, n = 31) [7].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The efficacy of cetuximab-containing regimens after the use of ICIs in R/M HNSCC has been recently reported, and this may be the result of a synergistic effect of ICIs and cetuximab, as described above. However, multiple regimens including cetuximab have been evaluated in these reports, and individual regimens were not considered [18,23]. This is the first report to describe the efficacy and safety of a regimen limited to Cmab + PTX after progression following ICI therapy, which has important implications for the optimization of the treatment sequence for R/M HNSCC.…”
Section: Discussionmentioning
confidence: 99%